Protestantism as the Guarantee of National Liberty in the Eighteenth-Century Britain - Yigit, Pervin; Özkutlu, Seyit (Journal of History Culture and Art Research, 2017)
In eighteenth-century, Britain was experiencing success in international arena, increase in economic conditions, improvement in education and developments in arts and sciences. However, especially the advance in natural sciences and the growing popularity of rationalism harmed the political, social and psychological power of religion during the aforementioned period. Due to the religious controversies, Protestant principles lost their crucial role in maintaining the political and social order in Great Britain. Besides internal threats, the country had experienced external threats –such as France- as well. The peril of France was also considered as a direct threat of Catholicism to the Anglican Church. Therefore, the Anglican Church needed to be defended against both the internal and external threats. As a result, the church was re-established as the basis of political and moral order by the attempts of Anglican thinkers and religious men. In order to show how Anglicans had promoted their religious principles, the works of John Brown (1715-1766) -one of the most influential religious men of the period- were analysed. The controversy between Protestantism and Catholicism, namely between Great Britain and France, led Brown to use Protestantism as the basis of English liberty and attack to Catholicism by means of the concept of “liberty” provided by Protestant principles. At this point Brown defended Anglicanism and indicate Anglican’s opposition to Catholicism in terms of liberty. The aim of this paper is to reveal how the concept of ‘liberty’ and Protestantism were used together in order to preserve the commonwealth in Great Britain. In addition, how the concept of liberty changed in John Brown’s works after the threat of Catholicism and became a social concept in the English Enlightenment is also examined.